2017
DOI: 10.1016/j.cub.2017.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Spatiotemporally Integrates Visual Signals to Control Saccades

Abstract: SUMMARY Like many visually active animals including humans, flies generate both smooth and rapid, saccadic movements to stabilize their visual gaze. How rapid body saccades and smooth movement interact for simultaneous object pursuit and gaze stabilization is not understood. We directly observed these interactions in magnetically-tethered Drosophila free to rotate about the yaw axis. A moving bar elicited sustained bouts of saccades following the bar, with surprisingly little smooth movement. By contrast, a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
159
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(177 citation statements)
references
References 48 publications
16
159
2
Order By: Relevance
“…In our initial experiments, the strength of vision- and wind-evoked turns were functions of flies’ starting orientations, with the strongest turns for each modality falling at distinct orientations. Similarly, turns that followed wind onsets and offsets in the pulse experiment were nonlinear functions of stimulus orientation — consi stent with a model based on spatial filtering, but not with a model based on orientation error [15,27,28]. Several observations also support differential temporal filtering of wind and visual cues.…”
Section: Discussionmentioning
confidence: 86%
“…In our initial experiments, the strength of vision- and wind-evoked turns were functions of flies’ starting orientations, with the strongest turns for each modality falling at distinct orientations. Similarly, turns that followed wind onsets and offsets in the pulse experiment were nonlinear functions of stimulus orientation — consi stent with a model based on spatial filtering, but not with a model based on orientation error [15,27,28]. Several observations also support differential temporal filtering of wind and visual cues.…”
Section: Discussionmentioning
confidence: 86%
“…For example, the first paper describing spontaneous saccades in tethered flight noted that flies perform saccades of unpredictable timing (i.e., spontaneous) much less frequently in the dark [2]. Also, it has recently been shown that magnetically tethered flies (who are free to rotate about their yaw axis) perform saccades in the direction of yaw optic flow or toward a visual object [8]. These saccades can be considered stimulus driven in that their average onset times can be predicted by a model that integrates optic-flow velocity, or visual-object position, over time.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report behaviors which cannot be described in the present framework. For example, saccades towards objects have different dynamics than turns in response to background motion (Mongeau and Frye, 2017), but our modeling assumes a fixed relation between visual output and motor response. Neurons within central complex have been recently shown to maintain an internal representation of the fly’s heading during walking, both in the presence or absence of visual cues Seelig and Jayaraman (2015); Green et al (2017); Turner-Evans et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation is problematic, since it has been shown that asymmetric motion detector models based on properties of a single type of visual neuron are able to mediate the responses associated to the position-dependent term as well as the responses associated to the motion-dependent term (Poggio and Reichardt, 1973, 1981; Fenk et al, 2014). More recently, it was shown that the dynamics of saccades in magnetically tethered Drosophila are different for objects and backgrounds (Mongeau and Frye, 2017), suggesting again that these behaviors are mediated by distinct circuits.…”
Section: Introductionmentioning
confidence: 99%